Coordinate measuring machines and systems - Hocken, Robert J.; Pereira, Paulo H. (Boca Raton, Fla. : CRC Press, 2012)
'Since John Bosh edited and published the first version of this book in 1995 the world of manufacturing and Coordinate Measuring Machines (CMMs) and Systems has changed considerably. In addition to two new editors, one from academia and one from a metrology intensive user industry, this second edition has many new authors and a known cadre of experts who have grown with the field since the last version. The well-rounded coverage includes the evolution of measurements and development of standards, the use of CMMs, accessory elements, application software, performance and financial evaluations, and accuracy'--
'Since John Bosch edited and published the first version of this book in 1995 the world of manufacturing and Coordinate Measuring Machines (CMMs) and Coordinate Measuring Systems (CMSs) has changed considerably. Perhaps most significantly we have seen a large volume of manufacturing move to Asia, particularly the Peoples Republic of China. We have also seen enormous growth in the capability of what were once called'micro' computers and the incredible strides in communication through the multifaceted ever changing marvel we call the World Wide Web. Add to that the proliferation and miniaturization of the cell phone, PDAs of all sorts, and digital books, etc. and much of the work we do and the tools we do it with would have seemed quite alien a decade and a half ago'--
Includes bibliographical references and index.
Keywords: Coordinate measuring machines; Dimensional analysis